2017
DOI: 10.1007/978-3-319-44588-5_6
|View full text |Cite
|
Sign up to set email alerts
|

How Much Knowledge Is Necessary for Action?

Abstract: How much knowledge is necessary for action? This question is fundamental because it suggests that the link between knowledge and action is debatable, that there is no given, fixed causal relationship between knowledge and action. In addition, there seems to be no fixed causal direction. Knowledge can be a prerequisite for action but also a consequence of an action. My opening question relates two key words in psychology. One of them is knowledge, about which a large body of knowledge exists (e.g., Halford, Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…The current findings are consistent with Funke's [12] argument that knowledge is a necessary antecedent of goal-oriented behaviors. He drew on the theory of planned behavior to support his argument, asserting that intention implies having knowledge about a behavior.…”
Section: Theoretical Implicationssupporting
confidence: 90%
See 1 more Smart Citation
“…The current findings are consistent with Funke's [12] argument that knowledge is a necessary antecedent of goal-oriented behaviors. He drew on the theory of planned behavior to support his argument, asserting that intention implies having knowledge about a behavior.…”
Section: Theoretical Implicationssupporting
confidence: 90%
“…Individuals often use information to formulate plans; thus, information is useful when individuals engage in planned behaviors [12]. Planned behaviors involve forethought, and often arise after individuals have formed behavioral intentions.…”
Section: The Theory Of Planned Behaviormentioning
confidence: 99%
“…According to the theory of planned behavior, the increased awareness and knowledge about the advantages of a given behavior does not in itself guarantee that individuals will perform the desired behavior. In fact, individuals must come forward, be willing for change, and feel empowered and ready to change (32).…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study showed that the iron supplementation training sessions were weakly held for female students in schools, and 64 students reported having at least one training session in this regard [23]. Obtaining the knowledge and information necessary to perform a behavior is one of the prerequisites for conducting behavior and it is necessary to obtain accurate information about the importance of the subject, the need to perform the intended behavior and learning how to behave correctly to continue conducting a behavior [29]. Increased knowledge and awareness increase in iron supplement intake [30].…”
Section: Discussionmentioning
confidence: 99%